Wearing of face masks while jogging during the COVID-19 pandemic: will my oxygenation decrease? - Ting, Frederic Ivan; Villanueva, Justine (International Journal Of Community Medicine And Public Health, 2020)
Since the start of the COVID-19 pandemic, several guidelines recommend the wearing of face masks when outdoors. However, it is still widely debated if that recommendation is safe while exercising outdoors. Our paper shows that the wearing of face masks while jogging outdoors does not significantly affect the level of the person’s oxygen saturation.